Mechanical aspects of heartbeat reversal in pupae of Manduca sexta - Sláma, K (Journal of insect physiology, 2003)
Pulsations of the dorsal vessel were investigated with new optocardiographic techniques based on the transmission and reflection of pulse-light through optic fibers. This noninvasive technique enabled simultaneous, in vivo multisensor recordings of the heartbeat without touching the pupal integument. There was a very regular heartbeat reversal with 3 distinctive phases: (a) a backward-oriented (retrograde) cardiac pulsation; (b) a forward-oriented (anterograde) pulsation with faster frequency; and (c) shorter or longer periods of temporary cardiac standstill that usually occurred after the termination of the anterograde phase. Occasionally, there were localized series of systolic cardiac contractions during the retrograde phase. Simultaneous recordings from the base and the tail of the abdomen revealed a reciprocal, "mirror image-like", quantitative relationship. The most intensive anterograde hemolymph flow occurred at the base while the most intensive retrograde flow occurred at the tail of the abdomen. The bi-directional switchovers of heartbeat (reversal) were occasionally associated with modifications during each of the unidirectional cardiac phases. Anterograde peristalsis showed a 2-fold higher frequency of pulsation in the thoracic aorta in comparison with the posterior parts of the heart. Thus, in addition to the "odd" peristaltic waves originating at the tail, there were intercallated "even" peristaltic waves originating in the middle of the abdomen. Both of them propagated hemolymph through the thoracic aorta into the head; the first waves took the hemolymph in from the distal end, while the second sucked it from the middle of the abdomen. The use of multiple optocardiographic sensors also enabled detection of cardiac pulsations on the opposite, ventral side of the body, within the ventral perineural sinus. The ventral side of the head showed only the presence of an anterograde pulse, whereas the ventral side of the tail exhibited a strong reciprocal retrograde phase and a very weak anterograde phase. These results explain why the existence of a periodic heartbeat reversal should be essential for circulatory functions at both extremities of the cylindrical insect body. In diapausing pupae, regular cycles of heartbeat reversal were substituted by prolonged periods of anterograde pulsation during the entire duration of bursts of CO2 release (average duration of the burst was 18-20 min, periodicity 5 to 18 h). The physiological nature of such feed-back correlation between heartbeat and metabolic CO2 production is not yet clear, because the anterograde heartbeat could be also induced by a number of nonspecific factors unrelated to CO2 (mechanical irritation, injury, injections, elevated temperature). During the postdiapause, developing pharate-adult stage, the correlation between CO2 and anterograde heartbeat completely disappeared. It has been concluded that regulation of insect heartbeat represents a highly coordinated, myogenic stereotype with inherent rhythmicity, which can be modified by a number of external and internal factors.
Keywords: Myocardial Contraction; technologie optických vláken; zvířata; pulz; hemolymfa; Heart Rate; Hemolymph; Manduca; Pulse; Metamorphosis, Biological; Pupa; kukla; Animals; Fiber Optic Technology; krevní oběh; Blood Circulation; Carbon Dioxide; biologická proměna; kontrakce myokardu; termografie; oxid uhličitý; srdeční frekvence; Thermography